2017
DOI: 10.1136/heartjnl-2016-311144
|View full text |Cite
|
Sign up to set email alerts
|

Platelet count and mean platelet volume predict outcome in adults with Eisenmenger syndrome

Abstract: Thrombocytopaenia significantly increased the risk of mortality in ES. Furthermore, raised MPV, severe secondary erythrocytosis and anaemia, but not platelet count, were associated with an increased risk of thrombotic events in our adult cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
0
19
1
1
Order By: Relevance
“…MPO also showed a positive, nominally significant (p = 0.03), association with PLT in FHS data ( Supplementary Table 2); furthermore, MPO knockdown MK clones showed a statistically significant decrease in MK derived platelet count, demonstrating a positive correlation between the protein and platelet production (Figure 3). MPO's positive correlation with both MPV and PLT is not concordant with the inverse relationship between MPV and PLT shown in prior literature 32 MCAM was negatively correlated with CHD risk in a prior MR study 18 . The MCAM instrumental variable SNP (rs11217234) in our study was nominally associated with (p = 0.027) with decreased risk of a second myocardial infarction event ( Supplementary Table 5).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…MPO also showed a positive, nominally significant (p = 0.03), association with PLT in FHS data ( Supplementary Table 2); furthermore, MPO knockdown MK clones showed a statistically significant decrease in MK derived platelet count, demonstrating a positive correlation between the protein and platelet production (Figure 3). MPO's positive correlation with both MPV and PLT is not concordant with the inverse relationship between MPV and PLT shown in prior literature 32 MCAM was negatively correlated with CHD risk in a prior MR study 18 . The MCAM instrumental variable SNP (rs11217234) in our study was nominally associated with (p = 0.027) with decreased risk of a second myocardial infarction event ( Supplementary Table 5).…”
Section: Discussioncontrasting
confidence: 40%
“…Seven proteins showed significant association with both PLT and MPV: soluble CD40 ligand (sCD40L), stromal cell-derived factor 1 (SDF1), pro-platelet basic protein (PPBP), translocation associated notch homolog (Notch1), adrenomedullin (ADM), glyceraldehyde 3-phosphate dehydrogenase (GAPDH), and cadherin-13 (CDH13). All seven proteins' direction of effect for MPV was the opposite of their direction of effect for PLT (Pearson's correlation: -0.90, 95% CI: (-0.99, -0.48)), reflecting the inverse correlation of MPV and PLT 32 .…”
Section: Fhs Protein-mpv/plt Association Analysesmentioning
confidence: 94%
“…Routine assessment of ES patients should include risk stratification, either using the criteria recommended by current European Society of Cardiology guidelines, and/or ES-specific predictors or outcome including BNP, C-reactive protein, platelet count and 6MWD. 2 , 36 38 In a multicentre study of 1098 ES patients, five independent predictors of mortality were identified: age, pre-tricuspid shunt, lower systemic oxygen saturations (SaO 2 ), presence of pericardial effusion and absence of sinus rhythm. 39 Patients at increased risk of death should be considered for PAH therapies, independent of FC.…”
Section: Methodsmentioning
confidence: 99%
“…Platelets mediate and initiate thrombotic occlusion of the whole coronary artery and accumulate in the circulation resulting in impaired microcirculation and provoking myocardial ischemia during reperfusion [ 19 ]. However, patients with AMI with low platelet counts are commonly older with several comorbidities in most cases [ 20 ]. Similarly, our study showed that the patients with low platelet counts were older and had a higher prevalence of diabetes mellitus, hypertension, and previous stroke which could lead to higher rates of ischemic events despite low platelet counts.…”
Section: Discussionmentioning
confidence: 99%